Kinesthetic Exchanges between Cinematographers and Dancers: A Series of Screendance Interviews - Alexander Petit Olivieri (The International Journal of Screendance, 2022)
This paper examines the kinesthetic exchanges between camera operators and dancers, and proposes that their creative methodologies and interpersonal relationships can enhance the making of a screendance. I discuss how I discovered this project, unpack the phrase “kinesthetic exchange,” and identify the cinematographer as the co-creator of a film’s kinesthesia. I also discuss screendances that prioritize mobile camera operation, and I speculate that shared kinesthesia between camera and dancer has the potential to kinesthetically and emotionally affect audiences. Included are six interviews of contemporary dance makers and filmmakers that speak to the kinesthetic connection between the dancer and camera operator, and how that relationship enlivens the two-dimensionality of the frame. It is my intention to offer varying perspectives about kinesthetic exchanges between camera operators and dancers, and how their relationships may influence the creative processes for the creation of screendances.
Keywords: camera operation; camera movement; co-creation; collaboration; improvisation; intimacy; intuition; kinesthetic exchange; light; observational practice; personal histories